Role of Multimedia Technologies in Training of Students - TAHAAN, Osama; SALEH, Hadi (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
The article presents the role of multimedia technology in teaching students,this article describes dignity of usage of multimedia technology in education andthe necessary guidelines to create such lessons.